Improved epicentral relocation in the offshore Campos basin, SE Brazil, with the RSTT 3D model - Neves, Felipe dos Anjos; Assumpção, Marcelo; Dourado, João Carlos [UNESP]; Le Diagon, Frank; Ortolan, Antonio (Elsevier, 2018)
Earthquake location on the continental shelf is often poor because: a) the seismic stations are mainly located on the continent, to one side of the epicenter (which means that any error in the velocity model causes a large epicentral error), and b) 1D models are commonly used in a region with strong lateral variations in the crustal structure. We tested the use of the 3D regional seismic travel time (RSTT) model to relocate an event of magnitude 3.8 mb that occurred on July the 1 st, 2010, in the Campos basin, southeast (SE) Brazil. This event was also recorded by a seismic vessel, which allowed an estimate of the azimuth of the incoming P-waves. The new location based on the 3D model is more consistent with the data recorded by the streamers, which shows that the use of 3D RSTT models can improve earthquake locations offshore. Several other events in the SE offshore basins were relocated with the 3D RSTT model, which confirmed the trend of epicenters lying beneath the continental slope where sediment thickness tends to be highest.
Keywords: Continental shelf; Regional 3D epicentral location; RSTT